Security signaling optimization in optical network for smart substation - Yuhao ZHAO; Xiaoguang HAO; Shaobo GENG; Peng LUO; Kun ZHOU; Jialin ZHEN; Yurong MAO (Dianxin kexue)
The communication security issue brought by smart substation is of great importance and should not be ignored in backbone optical networks.To solve this problem,firstly,the communication security challenges faced by optical networks in smart substation environment were analyzed,a signaling security optimization technique for optical networks for smart substation services was proposed.A so-called light-weighted security signaling scheme was designed to establish the end-to-end trusted connection.Under the environment of multi-domain communication services in smart substation,evaluation simulation for the signaling interaction was conducted.Simulation results show that the proposed approach can greatly enhance the security ability of multi-domain optical network with better performance in term of connection success rate.